PERFORMANCE OF EMPLOYEES : INDIVIDUAL CHARACTERISTICS AND WORK ENVIRONMENT IN PT KAWAI NIP - Esthi, Raniasari Bimanti (Journal of Research in Business, Economics, and Education, 2020)
Every employee has its own personality and distinctive characteristics, so that individual characters are formed for each employee. This individual characteristics if directed properly will improve employee performance. The work environment can also affect employee performance. This study aims to determine the effect of individual characteristics and work environment on employee performance. The sample is 60 employees of PT. Kawai Nip. The sampling technique uses random sampling. Data analysis using Structural Equation Model (SEM) with SmartPLS. The results show that individual characteristics influence employee performance. This is indicated by the T-statistic value of 20.258 and the path coefficient value is 0.770. While the value of T-statistics on the influence of the work environment on performance is obtained at 1.438 and the path coefficient value is 0.091. This means that the work environment does not affect employee performance.